An in-depth review: Unraveling the extraction, structure, bio-functionalities, target molecules, and applications of pectic polysaccharides - Pang, Yunrui; Peng, Zhigang; Ding, Kan (Carbohydrate polymers, 2024)
Pectic polysaccharides have long been a challenging subject of research in the field of macromolecular science, given their complex structures and wide range of biological effects. However, the extensive exploration of pectic polysaccharides has been limited due to the intricacy of their structures. In this comprehensive review, we aim to provide a thorough summary of the existing knowledge on pectic polysaccharides, with a particular focus on aspects such as classification, extraction methodologies, structural analysis, elucidation of biological activities, and exploration of target molecules and signaling pathways. By conducting a comprehensive analysis of existing literature and research achievements, we strive to establish a comprehensive and systematic framework that can serve as a reference and guide for further investigations into pectic polysaccharides. Furthermore, this review delves into the applications of pectic polysaccharides beyond their fundamental attributes and characteristics, exploring their potential in fields such as materials, food, and pharmaceuticals. We pay special attention to the promising opportunities for pectic polysaccharides in the pharmaceutical domain and provide an overview of related drug development research. The aim of this review is to facilitate a holistic understanding of pectic polysaccharides by incorporating multifaceted research, providing valuable insights for further in-depth investigations into this significant polymer. [Display omitted]